Endoscopic Endonasal Transsphenoidal Approach for Third Ventriculostomy in the Management of Obstructive Hydrocephalus. Issue 7 (October 2021) - Liu, Bolin; Zheng, Tao; Lv, Wenhai; Huang, Yuanzhi; Li, Baofu; Chen, Baoying; Wang, Binrong; He, Shiming
Abstract : Abstract: Endoscopic third ventriculostomy (ETV) is a safe and effective method for the management of obstructive hydrocephalus. Traditional approach is a transfrontal trajectory through the foramen of Monro to access and open the third ventricle floor. Though endoscopic endonasal transsphenoidal approach (EETA) for pituitary and skull base tumors has become increasingly popular, no published literature has explored its utility in performing an ETV. Here, the authors reported a successful ETV for obstructive hydrocephalus through the EETA. A 57-year-old male presenting with progressive headache and gait disturbance for 3 months was diagnosed with obstructive hydrocephalus. Brain MRI revealed an obstruction of cerebrospinal fluid (CSF) flow at the cerebral aqueduct and supratentorial hydrocephalus, accompanied with dilatation and downward herniation of the third ventricle floor. Considering the displacement of the third ventricle floor and the indication for surgery, an ETV was successfully performed through the EETA. No postoperative complication was observed. Both radiological and clinical evaluation postoperatively confirmed ETV success with decreased ventricular size, increased CSF flow across the floor of the third ventricle, and improved clinical signs. EETA is a feasible approach for ETV in selected cases of obstructive hydrocephalus. This approach provides a short trajectory to directly visualize and open the Liliequist's membrane and the displaced floor of the third ventricle, while minimizes damage to normal brain tissue. Skull base repair with nasoseptal flap ensures the success rate by preventing postoperative CSF leak and infection. Abstract : Supplemental Digital Content is available in the text